Estudio crítico de experiencias y su aplicación con prácticas innovadoras en la gestión municipal del cantón Latacunga - García Moreno, Gabriel (2023)
The objective of this project was to analyze municipal management from a critical study of its current operation and the innovation of its practices, which are oriented towards the search for effective improvement to achieve highly beneficial results for citizens, the particular delimitation of the study is He did it in the Latacunga canton. A bibliographic collection and analysis of each current strategy used in the institution was necessary in order to analyze the best alternatives in the international context studied to create the Social Innovation Plan, with specific benefits and a high sense of innovation in management. municipal, it was necessary to apply the qualitative methodology when developing an interview format with someone expert in the subject of municipal management, it was a quantitative investigation when preparing tables related to the opinion of the citizen-user through the application of a survey.